(3GdEOGQI GdUfGYjIs - (3bjS(B, (3GdeDefs; (3eMj GdOjf(B, (3Cejfs ((3YeGf(B:s (3OGQ RgQGf(B,s, 2005)
(3GdEOGQI GdUfGYjI(B-(3GdJfXje GdUfGYj(B-(3GdYedjGJ GdNGQLjI ddJfXje GdUfGYj(B-(3GdYedjGJ GdOGNdjI ddJfXje GdUfGYjs
Keywords: (3GdEOGQI GdUfGYjIs; (3GdJfXje GdUfGYjs; (3GdYedjGJ GdNGQLjIs; (3GdYedjGJ GdOGNdjIs